Coastal Mooring Observing Networks and Their Data Products: Recommendations for the Next Decade - Bailey, Kathleen; Steinberg, Craig; Davies, Claire; Galibert, Guillaume; Hidas, Marton; McManus, Margaret A.; Murphy, Teresa; Newton, Jan; Roughan, Moninya; Schaeffer, Amandine (Frontiers in Marine Science, 2019)
Instrumented moorings (hereafter referred to as moorings), which are anchored buoys or an anchored configuration of instruments suspended in the water column, are highly valued for their ability to host a variety of interchangeable oceanographic and meteorological sensors. This flexibility makes them a useful technology for meeting end user and science-driven requirements. Overall, societal needs related to human health, safety, national security, and economic prosperity in coastal areas are met through the availability of continuous data from coastal moorings and other complementary observing platforms within the Earth-observing system. These data streams strengthen the quality and accuracy of data products that inform the marine transportation industry, the tourism industry, fisheries, the military, public health officials, coastal and emergency managers, educators, and research scientists, among many others. Therefore, it is critical to sustain existing observing system networks, especially during this time of extreme environmental variability and change. Existing fiscal and operational challenges affecting the sustainability of observing networks will likely continue into the next decade, threatening the quality of downstream data and information products - especially those used for long-term monitoring, planning, and decision-making. This paper describes the utility of coastal moorings as part of an integrated coastal observing system, with an emphasis on stakeholder engagement to inform observing requirements and to ensure data products are tailored to user needs. We provide 10 recommendations for optimizing moorings networks, and thus downstream data products, to guide regional planners and network operators: 1. Develop strategies to increase investment in coastal mooring networks 2. Collect stakeholder priorities through targeted and continuous stakeholder engagements 3. Include complementary systems and emerging technologies in implementation planning activities 4. Expand and sustain water column ecosystem moorings in coastal locations 5. Coordinate with operators and data managers across geographic scales 6. Standardize and integrate data management best practices 7. Provide open access to data 8. Promote environmental health and operational safety stewardship and regulatory compliance 9. Develop coastal mooring observing network performance metrics 10. Routinely monitor and assess the design of coastal mooring networks